Harnessing mRNA for the expression of monoclonal IgG and IgA in non-human primates - Rouzeau, Romy; Schmidt, Hayden R.; Deal, Cailin E.; Allen, Joel D.; Dudley, Dawn M.; Burton, Iszac; Rakasz, Eva G.; Plante, Obadiah; Crispin, Max; Carfi, Andrea; Sok, Devin (Frontiers in Immunology, 2026)
BackgroundMonoclonal antibodies (mAbs) are an increasingly essential class of medicines across many disease areas. In the human body, there are five antibody isotypes, each with potential therapeutic benefits for different disease indications. However, 97% of all clinically approved mAbs are produced as the IgG isotype, largely due to challenges associated with recombinantly producing non-IgG isotypes like IgM or IgA, which have additional N-linked glycan sites and can present as multivalent oligomers. One potential way to circumvent this challenge is to express mAbs in situ using mRNA encapsulated in lipid nanoparticles (LNP), bypassing the need for recombinant protein production.ObjectiveHere, we demonstrate the feasibility of expressing a mAb as both IgG and IgA in non-human primates (NHPs) using mRNA-LNPs.MethodsWe express ePGDM1400v9, a broadly neutralizing mAb targeting human immunodeficiency virus (HIV), in both IgG1 and IgA2 formats by infusing NHPs with LNPs containing the appropriate mRNAs.ResultsThough IgA2 expression levels were low, both formats were detectable in serum within one day of LNP infusion in all NHPs, and both were detectable in mucosal secretions of most animals. Importantly, serum mRNA-produced IgG1 and IgA2 retained HIV-neutralizing function. Furthermore, mass spectrometry analysis confirmed that mAbs of either isotype produced in situ exhibited glycosylation patterns highly similar to that of native antibody, which is likely to confer therapeutic advantages.ConclusionAltogether, this work demonstrates that mRNA-LNPs can be used to express native like mAbs of non-IgG isotypes in primates at detectable levels and enables further development and optimization of non-IgG mAb constructs.